THE FEATURES OF ORGANIZATION OF INDEPENDENT WORK OF FUTURE PHARMACEUTISTS IN THE PROCESS OF LEARNING ORGANIC CHEMISTRY WITH THE USE OF THE MOODLE SYSTEM - Oksana Golovchenko ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
Pursuing the goal of improving the quality of professional training of future specialists in higher pharmaceutical education is a current trend in Ukraine, which seems to determine the effectiveness of pharmaceutical services as a component of medical reform. A study of best practices of the organization of independent work of the future pharmacists in Organic Chemistry run at Bohomolets National Medical University, National Pirogov Memorial Medical University (Vinnytsya), Odessa National Medical University, I. Horbachevsky Ternopil State Medical University, National University of Pharmacy and revealed that distance learning is commonly used there as the form of organisation and implementation of educational process. The examination of the web-sites of M(P)HEIs of Ukraine made it possible to find out that the key specifics of the organization of independent work of students of pharmaceutical faculties in Organic Chemistry through distance learning is the use of the MOODLE system. Its selection is supported by the fact it that MOODLE meets the main requirements for its implementation and using in the higher education process. It is reliable in operation, easy to use and manage the educational process (including the organization of independent work of students), and characterised by modularity, compatibility, safety. In addition, the MOODLE system has the reasonable price of software, maintenance and hardware.